Employment, Identity and the Politics of Skills in Nunavut - Quintal-Marineau, Magalie (Études Inuit Studies, 2025)
Over the past decades, social policy in the Canadian Arctic has increasingly emphasized Inuit employability, largely through vocational training and skills development programs. While these initiatives aim to reduce unemployment and integrate Inuit into the formal economy, they often overlook how notions of “skills” intersect with Inuit cultural values and lived experiences. This paper explores how concepts of competence, merit, and knowledge are interpreted and negotiated within the Nunavut Public Service (NPS). Drawing on interviews with current and former Inuit public servants, the study examines how institutional definitions of work, learning, and expertise shape – and are shaped by – Inuit worldviews. Four main themes emerge from participants’ testimonies: (1) cultural wellbeing; (2) diverging understandings of work; (3) career aspirations and contributions; and (4) knowledge and experience hierarchy. These findings challenge deficit-based narratives and call for a rethinking of labour frameworks through the lens of Inuit identity, governance, and self-determination. The paper argues that power relations embedded in dominant skill assessments contribute to structural barriers, and that re-centering Inuit ways of knowing is essential for equitable workforce participation and economic autonomy in Nunavut.